2006
DOI: 10.1007/s10620-006-9614-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional Response of Hepatocytes Transplanted into Gunn Rats Stimulated with Thyroid Hormone

Abstract: In the attempt to translate laboratory studies into clinical practice, the small number of cells that can be transplanted is currently a problem to be solved. The aim of this work is to study the functional response of intrasplenically transplanted syngeneic rat adult and fetal hepatocytes to a proliferative stimulus, 3,5,3'-triiodothyronine. Total serum bilirubin significantly decreased from 7 to 90 days after fetal hepatocyte transplantation and from 24 hr to 30 days after adult hepatocyte transplantation. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Subsequently, deficiency of UGT1A1 was identified, representing a relevant phenocopy of CN I syndrome (McCandless 2011). A number of preclinical HTx studies have shown efficacy in this model, including application of immortalized hepatocytes, bone marrow-derived cells, as well as intrasplenic administration of both fetal and adult hepatocytes (Kawashita et al 2008); (Muraca et al 2007); (Cubero et al 2007); (Guha et al 2002). In these studies, engraftment advantage was achieved by irradiation, partial hepatectomy, or induction of ischemic/reperfusion injury to damage endogenous tissue.…”
Section: Htx For Inherited Metabolic Diseasesmentioning
confidence: 99%
“…Subsequently, deficiency of UGT1A1 was identified, representing a relevant phenocopy of CN I syndrome (McCandless 2011). A number of preclinical HTx studies have shown efficacy in this model, including application of immortalized hepatocytes, bone marrow-derived cells, as well as intrasplenic administration of both fetal and adult hepatocytes (Kawashita et al 2008); (Muraca et al 2007); (Cubero et al 2007); (Guha et al 2002). In these studies, engraftment advantage was achieved by irradiation, partial hepatectomy, or induction of ischemic/reperfusion injury to damage endogenous tissue.…”
Section: Htx For Inherited Metabolic Diseasesmentioning
confidence: 99%
“…The development of strategies to give transplanted hepatocytes a selective advantage for proliferation over the cells of the recipient's liver is proving to be a difficult task [Cubero et al, 2007]. In many cases, the possibility of injecting cells in several locations would enhance the therapeutic potential of cell therapy, either because it helps to enlarge the tissue mass bringing it to the critical one or because it helps the generation of immunological tolerance.…”
Section: Discussionmentioning
confidence: 99%